Funktionellt och attraktivt boende i Gällivare : Bostadstyper, funktioner och attraktivitet - Rynbäck, Sofie (2011)
Malmberget is a town of Gällivare municipality who is facing a situation which virtually all of the central parts have to be demolished or moved because of the mining industry. In the current situation is a lack of available housing in the community and because of the situation in Malmberget the municipality will require more housing. The purpose of this paper is to develop a basis that will provide support for Gällivare municipality in their continuing work with the ongoing transformation of society and for future housing planning in the municipality. The work identifies housing types and tenures that are demanded by the inhabitants of the town. The study also considers the functions that are in demand on new homes and the characteristics of an attractive housing area in Gällivare. The goal is to find the features of homes and properties in residential areas which make Gällivare a more attractive community where residents feel satisfied and want to stay. In order to identify what residents require for new housing and residential areas, a survey and interviews was made. A quantitative survey was conducted, where the inhabitants of the town was divided into four subgroups based on age. A random selection was made in the different age groups and this generated 100 people in each sample, a total of 400 people. Qualitative interviews were also made with some of the largest housing companies, Top Bostäder, FAB, TN bygg och fastighet, Riksbyggen and HSB. Housing types that are most attractive is a villa or a centrally located apartment, the retired persons can also think of moving to senior housing. Brand new villa homes are most popular, among young people and families with children, while 49-79 year olds prefer apartments in the existing housing stock. It has also emerged from the survey that a higher proportion wants to rent their future homes than what the distribution looks like in the current situation. Most of the residents in Gällivare, Malmberget and Koskullskulle want according to the questionnaire live in ...